Bio-response of copper-magnesium co-substituted mesoporous bioactive glass for bone tissue regeneration - Anand, Akrity; Kaňková, Hana; Hájovská, Zuzana; Galusek, Dušan; Boccaccini, Aldo R.; Galusková, Dagmar (Journal of Materials Chemistry B, 2024)
Mesoporous bioactive glass (MBG) is widely acknowledged in bone tissue engineering due to its mesoporous structure, large surface area, and bioactivity. Recent research indicates that introduction of metallic ions has beneficial impacts on bone metabolism and angiogenesis. Thus, the features of MBG can be modified by incorporating combinations of ions, such as magnesium (Mg) and copper (Cu), which can play a considerable role in bone formation, influencing angiogenesis, osteogenesis, as well as antibacterial properties. In this study, Mg and Cu were co-doped for the first time (in a ratio of 1 : 1) in 80SiO2-5P2O5-(15 − 2x)CaO-xMgO-xCuO glass composition with x = 0, 0.5, 1, and 2 mol%, synthesized using the sol-gel and evaporation-induced self-assembly method. X-ray diffraction analysis confirmed the amorphous nature of the powders, while inductively coupled plasma-optical emission spectrometry verified the existence of dopant ions in the respective amounts. The nitrogen sorption method indicated the formation of uniform cylindrical mesopores which are open at both ends and a high surface area of the powders. TEM images show fringes, indicating an ordered mesoporous structure in all MgCu co-doped systems. In vitro bioactivity was observed in all MBG powders, confirmed by the formation of an apatite phase when placed in simulated body fluid (SBF). Flake-like microstructure characteristics of HAp crystals found on the surface of MBG powders were visualized using FESEM. Cytotoxicity tests at lower concentrations (0.1 and 1 wt/vol%) of co-doped 2MC MBG (co-doping up to 2 mol%) showed cell proliferation and viability of osteoblast-like MG-63 cells and normal human dermal fibroblast (NHDF) cells similar to the basic glass 80S. Antibacterial study of MBG pellets showed an increment in the zone of inhibition with the sequential addition of doping ions. The turbidity measurement of bacterial cultures revealed that the optimal concentration for effectively inhibiting bacterial growth was 1 wt/vol% (i.e., 10 mg mL−1) concentration of MBG extracts. The result suggested that the incorporation of Mg and Cu ions in MBG in lower concentrations of up to 2 mol% can be useful in bone regeneration owing to bioactivity, cell proliferation, and antibacterial characteristics.
CRIS-Team Scopus Importer:2024-02-16